Effectiveness of Vitamin C for Iron Supplementation in Patients with Iron Deficiency Anemia - Aneel Kumar, Madam Yasmin Kousar, Asad Mahmood Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Anaemia is a condition in which the number of red blood cells is insufficient to meet physiologic needs; it is caused by many conditions, particularly iron deficiency. Objectives: The main objective of the study is to find the effectiveness of vitamin C for iron supplementation in patients with iron deficiency anemia. Material and methods: This cross sectional study was conducted in Chandka Medical College Hospital Larkana during February, 20220 to March 2021 with the permission of ethical committee of hospital. Data were collected from 100 patients suffering from iron deficiency anemia (IDA). Participants were selected through randomly sampling technique. Results: The data was collected from 100 patients and mean age was 45.67±5.81 years. The only factors which emerged as statistically significant from the adjusted logistic regression analysis model were insufficient intakes of iron (OR = 7.39; 95% CI: 1.45-37.57) and vitamin C (OR = 6.14; 95% CI: 1.34-28.27), frequent (≥2 times per week) tea consumption (OR = 0.01; 95% CI: 0.01-0.08), infrequent (≤2 times per week) red meat consumption (OR = 3.71; 95% CI: 1.01-13.61), and the possession of a personal history of IDA (OR = 6.00; 95% CI: 1.45-24.76). Conclusion: It is concluded that main risk factors in relation to contracting anemia were inadequate intakes of iron and vitamin C, frequent tea consumption, infrequent red meat consumption, and a past personal history of IDA. Keywords: Patients, Anemia, Hb, Iron